Rare Presentation of Congenital Cystic Adenomatoid Malformation of the Lung - Sharma, Anubha; Pannu, MS; Lata, Neeraj; Dhillon, SPS; Singh, Narinder; Sareen, Ashwini (Journal of Nepal Paediatric Society, 2016)
Congenital cystic adenomatoid malformation is a rare entity presenting with respiratory difficulty in newborns and even later in infancy. Various cases have been reported but recurrent spontaneous pneumothorax in an infant with failure to thrive and pectus carinatum since birth(with uneventful antenatal history and asymptomatic course in the first seven months of life) is an extremely rare presentation of this congenital lung condition. J Nepal Paediatr Soc 2016;36(1):91-93.